Characterization and Photoresponse Propreties of Sn-doped ZnO Thin Films - Krisana Chongsri; Chatpong Bangbai; Wicharn Techitdheera; Wisanu Pecharapa (My University, 2013)
Sn-doped ZnO (SZO) thin films were prepared by sol-gel spin-coating method based on zinc acetate dihydrate (CH3COO)2 Zn H2O, Tin (IV) chloride pentahydrate (SnCl45H2O), 2-methoxyethanol (C3H8O2) and diethanolamine ((HOCH2CH2)2NH, DEA.The solution was prepared with various Sn doping content in ZnO assigned at 2%, 4%, 6%, 8% and 10%. All films were spin-coated on borosilicate substrates and annealed temperature at 550 °C for 4 h in air. The structural properties of the films were characterized by XRD and SEM and the corresponding results indicated the crystalline structure and surface morphology of the films, respectively. UV-VIS transmission spectra was used to determine optical properties of as-prepared. The increasing Sn doping content into ZnO films results to the enhancement in transparency of the films and the observable alternation in their grain size. The photoilluminated current linearly increases with increasing bias voltage indicating the good Ohmic contact of the device. The photoresponse of the device has significant improvement with increasing Sn doping content.
Keywords: Spin Coating; Ohmic contact; Borosilicate glass; ZnO doping and properties